Performance of composite sand cement brick containing recycled concrete aggregate and waste polyethylene terepthalate - Azmi, Nurul Bazilah (2018)
The reuse and recycling of waste materials from construction and demolition waste is one of the new concepts for brick manufacturing production. Construction and demolition debris refers to waste materials that result from the construction, renovation and demolition of buildings. Bricks are an important material for developing areas where manufacturers find it difficult to locate adequate sources due to the shortage of natural aggregate supply. Construction waste can be recycled to replace naturals resource or other competitive materials. This study aims to establish the sustainable properties for composite bricks using Recycle Concrete Aggregate (RCA) and Polyethylene Terephthalate (PET) waste bottles as sand aggregate replacement. RCA was obtained from crushed laboratory concrete cubes while PET bottles were collected around UTHM and Parit Raja areas. The objectives of this study are to determine the optimum cement-sand ratio ( 1 :5, I :6 and 1 :7) for composite brick through density, compressive strength and water absorption tests, to investigate the mechanical properties and durability of composite sand cement bricks through shrinkage and carbonation tests, and to identify the optimum percentages of RCA and PET as sand aggregate replacement in composite bricks. For this study, the brick specimens were prepared using 25%, 50% and 75% of RCA and 1.0%, 1.5%, 2.0% and 2.5% of PET by volume of natural sand with a water-cement ratio of 0.6. The size of the RCA used measured less than 5 mm. Moreover, the size of the sieved waste PET granules was between 0.1 to 5 mm which made it physically similar to the size of fine aggregates. The bricks were cast in moulds measuring 215 mm in length, I 03 mm in width, and 65 mm in depth. Three types of sand-cement ratios were used, namely I :5, I :6 and I :7. The first stage of the study was the determination of the best sand-cement ratio through density, water absorption and compressive strength tests. The next stage was the determination of the optimum percentages of RCA and PET according to the shrinkage and carbonation tests. The overall results revealed that the best cement-sand ratio was 1 :6. The density test indicates that the average density of composite bricks is lower compared to that of control bricks. The cement-sand ratio of I :6 was the optimum value for all sample bricks. In addition, the percentage of water absorption for composite bricks was found to be satisfactory. It can be concluded that the optimal replacement of RCA and PET was R25P I with a cement-sand ratio of I :6 as it achieved the lowest values during the drying shrinkage and carbonation tests.